Social bonding: regulation by neuropeptides - Lieberwirth, Claudia; Wang, Zuoxin (Frontiers in Neuroscience, 2014)
Affiliative social relationships (e.g., among spouses, family members, and friends) play an essential role in human society. These relationships affect psychological, physiological, and behavioral functions. As positive and enduring bonds are critical for the overall well-being of humans, it is not surprising that considerable effort has been made to study the neurobiological mechanisms that underlie social bonding behaviors. The present review details the involvement of the nonapeptides, oxytocin (OT) and arginine vasopressin (AVP), in the regulation of social bonding in mammals including humans. In particular, we will discuss the role of OT and AVP in the formation of social bonds between partners of a mating pair as well as between parents and their offspring. Furthermore, the role of OT and AVP in the formation of interpersonal bonding involving trust is also discussed.